Ischaemic enteritis in a patient with chronic renal failure: diagnosis and management decisions. (28th October 2010) - Yu, Jihan; Kim, Biro; Chung, Sungjin; Park, Cheol Whee; Chang, Yoon Sik
Abstract : Ischaemic enteritis is rare in patients with chronic renal failure not on dialysis. Here we report a case of ischaemic enteritis in an 81-year-old woman with chronic renal failure secondary to hypertension (not dialysis dependent) who presented with acute onset of abdominal pain, non-bloody diarrhoea and subsequent oliguria. The abdominal CT with angiography showed diffuse segmental wall thickening and decreased perfusion of the long segment of the ileum, with decreased enhancement of the vessels that supply the distal ileum. The clinical diagnosis of ischaemic enteritis was made. The patient responded initially to total parenteral nutrition and intravenous antibiotics. After the initiation of haemodialysis, because of the oliguria, the ischaemic enteritis progressed to bowel infarction, and an open laparotomy was performed. This report illustrates some of the difficult therapeutic decisions in a patient with ischaemic enteritis and chronic renal failure.